2000
DOI: 10.1016/s0022-2275(20)31967-2
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-binding proteins modulate ligand-dependent trans-activation by peroxisome proliferator-activated receptors and localize to the nucleus as well as the cytoplasm

Abstract: Peroxisome proliferator-activated receptors (PPARs) are activated by a variety of fatty acids, eicosanoids, and hypolipidemic and insulin-sensitizing drugs. Many of these compounds bind avidly to members of a family of small lipid-binding proteins, the fatty acid-binding proteins (FABPs). Fatty acids are activated to CoA esters, which bind with high affinity to the acyl-CoA-binding protein (ACBP). Thus, the availability of known and potential PPAR ligands may be regulated by lipid-binding proteins. In this rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…Wy14643 at concentrations at or below 10 mM exhibited PPARa selectivity, and L165041 at concentrations below 50 nM was a potent and highly speci®c activator of PPARd. In transactivation experiments using mouse PPARs, we found that TTA most ef®caciously activated PPARa (Helledie et al, 2000). 1 In this study using human PPARs we observed that TTA more ef®caciously and potently activated PPARd, whereas TTA-dependent activation of PPARa and PPARg was more modest.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Wy14643 at concentrations at or below 10 mM exhibited PPARa selectivity, and L165041 at concentrations below 50 nM was a potent and highly speci®c activator of PPARd. In transactivation experiments using mouse PPARs, we found that TTA most ef®caciously activated PPARa (Helledie et al, 2000). 1 In this study using human PPARs we observed that TTA more ef®caciously and potently activated PPARd, whereas TTA-dependent activation of PPARa and PPARg was more modest.…”
Section: Discussionmentioning
confidence: 60%
“…HaCaT cells were transfected with a PPAR-responsive reporter construct and PPAR expression vectors, and then treated with Wy14643, L165041, and BRL49653, which are selective for PPARa, PPARd, and PPARg, respectively (Kliewer et al, 1994(Kliewer et al, , 1995Forman et al, 1995;Lehmann et al, 1995;Berger et al, 1999). In addition, we included the thiasubstituted fatty acid analog TTA that in a concentrationdependent manner has been shown to activate all three murine PPAR subtypes (Helledie et al, 2000). 1 Figure 4 illustrates the selectivity, ef®cacy, and potency of the different ligands.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports also showed that FABP5 also localizes to the nucleus (Helledie et al, 2000;Napoli, 2016. The different results of FABP5 subcellular localization might be due to the different cell types. Since we observed that FABP5 is a cytoplasmic protein and the stimulation of FABP5 on SREBP-1c gene expression depends on its ability to effectively transport fatty acids, we speculate that fatty acids transported into cells by FABP5 directly or indirectly stimulate SREBP-1c gene expression.…”
Section: Discussionmentioning
confidence: 89%
“…Fatty Acid Binding Protein 5 (FABP5), one of the FABPs expressed in macrophages, is suggested to sequester antiinflammatory mediators from their target, creating a pro-inflammatory environment. [20][21][22] However, we have shown that FABP5-deficient mice develop increased inflammation following influenza A infection that persists long after wild type mice recovery, 23 likely indicating a complex role for FABP5 in modulating inflammatory responses in vivo.…”
Section: Introductionmentioning
confidence: 90%